Makna Asosiatif dalam Lagu Lihat Kebunku (Taman Bunga) Karya Aku Jeje: Kajian Semantik - Gracella, Arinda; Suseno, Asterina Akbariani; Rahmania, Firli Azkiya; Juansah, Dase Erwin; Firmansyah, Dodi (Kajian Linguistik dan Sastra, 2026)
This study aims to describe the types and functions of associative meanings in the lyrics of the song "lihat Kebunku (Flower Garden)" by Aku Jeje based on Leech's classification, and to explain how natural symbols are used to represent human emotions in the lyrics. The background of the study stems from the need for semantic analysis of song lyrics that are reinterpreted with new emotional nuances, but have not been widely studied academically. The method used is descriptive qualitative with data sources in the form of song lyrics that are analyzed through repeated reading techniques, recording elements of meaning, grouping categories, and interpreting connotative, affective, stylistic, social, and combined meanings. The results of the study show that there are 22 data containing associative meanings, consisting of 9 connotative meanings, 9 affective meanings, 1 stylistic meaning, 1 combined stylistic-connotative meaning, 1 combined connotative-affective meaning and 1 social meaning. These meanings are built through natural metaphors such as garden, flower, jasmine, gray, lay, bloom, and garden of the heart that represent love, loss, emotional vulnerability, and sincerity. Abstrak Penelitian ini bertujuan mendeskripsikan jenis dan fungsi makna asosiatif dalam lirik lagu Lihat Kebunku (Taman Bunga) versi Aku Jeje berdasarkan klasifikasi Leech, serta menjelaskan bagaimana simbol-simbol alam digunakan untuk merepresentasikan emosi manusia dalam lirik tersebut. Latar belakang penelitian berangkat dari kebutuhan analisis semantik terhadap lirik lagu yang direinterpretasi dengan nuansa emosional baru, namun belum banyak menjadi objek kajian akademik. Metode yang digunakan adalah deskriptif kualitatif dengan sumber data berupa lirik lagu yang dianalisis melalui teknik membaca berulang, pencatatan unsur makna, pengelompokan kategori, serta penafsiran makna konotatif, afektif, stilistika, sosial, dan gabungan makna. Hasil penelitian menunjukkan bahwa terdapat 22 data yang mengandung makna asosiatif, terdiri atas 9 makna konotatif, 9 makna afektif, 1 makna stilistika, 1 makna gabungan stilistika-konotatif, 1 makna gabungan konotatif-afektif serta 1 makna sosial. Makna-makna tersebut dibangun melalui metafora alam seperti kebun, bunga, melati, kelabu, layu, mekar, dan taman hati yang merepresentasikan cinta, kehilangan, kerentanan emosional, hingga keikhlasan.